2009
DOI: 10.1111/j.1749-6632.2009.04372.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Foxg1 in the Development of Neural Stem Cells of the Olfactory Epithelium

Abstract: The olfactory epithelium (OE) of the mouse is an excellent model system for studying principles of neural stem cell biology because of its well-defined neuronal lineage and its ability to regenerate throughout life. To approach the molecular mechanisms of stem cell regulation in the OE, we have focused on Foxg1, also known as brain factor-1, which is a member of the Forkhead transcription factor family. Foxg1 −/− mice show major defects in the OE at birth, suggesting that Foxg1 plays an important role in OE de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…As part of anterior neural plate pattern patterning several transcription factors are expressed in the olfactory sensory system, including the future telencephalon and OP. The Foxg1 transcription factor is expressed in both the olfactory sensory precursors and telencephalic precursors in both mouse and zebrafish (Danesin et al, 2009; Kawauchi et al, 2009; Danesin and Houart, 2012; Zhao et al, 2009). The loss of function of Foxg1 in knock-out mice leads to loss of the entire olfactory system including the OE, bulb and vomeronasal organ (Duggan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As part of anterior neural plate pattern patterning several transcription factors are expressed in the olfactory sensory system, including the future telencephalon and OP. The Foxg1 transcription factor is expressed in both the olfactory sensory precursors and telencephalic precursors in both mouse and zebrafish (Danesin et al, 2009; Kawauchi et al, 2009; Danesin and Houart, 2012; Zhao et al, 2009). The loss of function of Foxg1 in knock-out mice leads to loss of the entire olfactory system including the OE, bulb and vomeronasal organ (Duggan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating proliferation, differentiation, and possibly survival of neural progenitor cells, FoxG1 promotes axonal growth in the developing retina (Xuan et al, 1995; Trejo et al, 2004; Picker et al, 2009), regulates patterning of the developing forebrain (Xuan et al, 1995; Danesin et al, 2009), and is necessary for the proper formation of the inner ear (Pauley et al, 2006; Hwang et al, 2009), as well as the olfactory system (Duggan et al, 2008; Kawauchi et al, 2009a,b). Several recent studies have found that FoxG1 mutations are associated with the congenital form of Rett syndrome, a severe neurodevelopmental disorder (Jacob et al, 2009; Mencarelli et al, 2009, 2010; Philippe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Foxg1 encodes for a winged-helix TF expressed by rostral CNS and sense organs, crucial for their morphogenesis [43][44][45][46][47][48]. It is involved in several aspects of telencephalic development, including specification of the telencephalic field [49], specification of basal ganglia, paleo-and neo-cortex [48,50,51], and cortical laminar specification [21,52].…”
Section: Introductionmentioning
confidence: 99%